Trimethyllysine, a trimethylamine N-oxide precursor, provides near- and long-term prognostic value in patients presenting with acute coronary syndromes. (23rd April 2019) - Li, Xinmin S; Obeid, Slayman; Wang, Zeneng; Hazen, Benjamin J; Li, Lin; Wu, Yuping; Hurd, Alex G; Gu, Xiaodong; Pratt, Alan; Levison, Bruce S; Chung, Yoon-Mi; Nissen, Steven E; et al.
Abstract: Aims : Trimethyllysine (TML) serves as a nutrient precursor of the gut microbiota-derived metabolite trimethylamine N-oxide (TMAO) and is associated with incident cardiovascular (CV) events in stable subjects. We examined the relationship between plasma TML levels and incident CV events in patients presenting with acute coronary syndromes (ACS). Methods and results : Plasma levels of TML were quantified in two independent cohorts using mass spectrometry, and its relationship with CV events was investigated. In a Cleveland Cohort ( N  = 530), comprised of patients presenting to the emergency department with chest pain and suspected ACS, TML was associated with major adverse cardiac events (MACE, myocardial infarction, stroke, need for revascularization, or all-cause mortality) over both 30 days [3rd tertile (T3), adjusted odds ratio (OR) 1.77, 95% confidence interval (CI) 1.04–3.01; P  < 0.05] and 6 months (T3, adjusted OR 1.95, 95% CI 1.15–3.32; P  < 0.05) of follow-up independent of traditional CV risk factors and indices of renal function. Elevated TML levels were also associated with incident long-term (7-year) all-cause mortality [T3, adjusted hazard ratio (HR) 2.52, 95% CI 1.50–4.24; P  < 0.001], and MACE even amongst patients persistently negative for cardiac Troponin T at presentation (e.g. 30-day MACE, T3, adjusted OR 4.49, 95% CI 2.06–9.79; P  < 0.001). Trimethyllysine in combination with TMAO showed additive significance for near- and long-term CV events, including patients with 'negative' high-sensitivity Troponin T levels. In a multicentre Swiss Cohort ( N  = 1683) comprised of ACS patients, similar associations between TML and incident 1-year adverse cardiac risks were observed (e.g. mortality, adjusted T3 HR 2.74, 95% CI 1.28–5.85; P  < 0.05; and MACE, adjusted T3 HR 1.55, 95% CI 1.04–2.31; P  < 0.05). Conclusion : Plasma TML levels, alone and together with TMAO, are associated with both near- and long-term CV events in patients with chest pain and ACS.